Long-term exposure to circulating platinum is associated with late effects of treatment in testicular cancer survivors - Boer, H. (Ann Oncol, 2015)
BACKGROUND: The success of cisplatin-based (Platinol, Bristol-Myers Squibb Company, New York, NY, USA) chemotherapy for testicular cancer comes at the price of long-term and late effects related to healthy tissue damage. We assessed and modelled serum platinum (Pt) decay after chemotherapy and determined relationships between long-term circulating Pt levels and known late effects. PATIENTS AND METHODS: In 99 testicular cancer survivors, treated with cisplatin-based chemotherapy, serum and 24-h urine samples were collected during follow-up (1–13 years after treatment). To build a population pharmacokinetic model, measured Pt data were simultaneously analysed, together with cisplatin dose, age, weight and height using the NONMEM software. Based on this model, area under the curve between 1 and 3 years after treatment (Pt AUC(1–3 years)) was calculated for each patient. Predicted long-term Pt exposure was related to renal function and to late effects of treatment assessed median 9 (3–15) years after chemotherapy. RESULTS: Decay of Pt was best described by a two-compartment model. Mean terminal T(1/2) was 3.7 (range 2.5–5.2) years. Pt AUC(1–3 years) correlated with cumulative cisplatin dose, and creatinine clearance before and 1 year after treatment. Patients with paraesthesia had higher Pt AUC(1–3 years) (30.9 versus 27.0 µg/l month) compared with those without paraesthesia (P = 0.021). Patients with hypogonadism, elevated LDL-cholesterol levels or hypertension also had higher Pt AUC(1–3 years). CONCLUSIONS: Renal function before and after cisplatin treatment is an important determinant of long-term Pt exposure. Known long-term effects of testicular cancer treatment, such as paraesthesia, hypogonadism, hypercholesterolaemia and hypertension, are associated with long-term circulating Pt exposure.